Visual Archives and the Writing of Canadian History: A Personal Review - Burant, Jim (Archivaria, 2002)
Basing his arguments on more than twenty-five years of experience with visual archives, the author focuses on issues relating to visual archives and the writing of Canadian history over the past three decades. A review is undertaken of the use made by academic researchers of images from visual archives – primarily from the art and photography holdings of the National Archives of Canada – in historical publications over the past quarter century; and of how some current practitioners in such fields as art history, geography, and the social and environmental sciences, among others, are using such visual imagery as part of their research and analysis. A survey of available literature relating to visual archives is included. These sections are followed by a discussion of the dialogue which must develop between archivists and other professions in order to make such visual imagery, particularly photography, an integral part of the creation of meaningful interpretations of our history and our public memory. RÉSUMÉ En fondant ses arguments sur plus de vingt-cinq ans d’expérience avec les archives visuelles, l’auteur analyse la question des liens entre les archives visuelles et l’écriture de l’histoire canadienne dans les trois dernières décennies. Il passe en revue l’usage fait par les chercheurs universitaires, dans les publications du dernier quart de siècle, des images tirées des archives et principalement des fonds d’art et de photographies des Archives nationales du Canada. L’article démontre comment certains spécialistes actuels dans les domaines de l’histoire de l’art, de la géographie et des sciences sociales ou de l’environnement, entre autres, utilisent une telle imagerie visuelle dans leur recherche et leur analyse. Un relevé de la littérature disponible relative aux archives visuelles suit. L’auteur poursuit avec un examen du dialogue qui devrait se développer entre les archivistes et les autres professionnels afin que les archives visuelles, et particulièrement les photographies, deviennent une partie intégrante de la création d’interprétations significatives de notre histoire et de notre mémoire collective.